Checklist of the earthworm fauna of Bosnia & Herzegovina (Oligochaeta: Lumbricidae) - Sekulić, Jovana; Stojanović, Mirjana; Popović, Filip; Trakić, Tanja (Zootaxa, 2022)
In this paper, a list of the earthworm fauna of Bosnia & Herzegovina (Oligochaeta: Lumbricidae) is presented, including literature data, unpublished data from our collection and new data from the field. In this list, earthworm diversity, general ecology, their distribution and zoogeographical types are presented as well. The currently known earthworm fauna of Bosnia & Herzegovina is comprised of 49 species belonging to 12 genera, with Dendrobaena being the species-richest genus (11). Our zoogeographic analysis has shown presence of 9 different types of distribution. Аlmost one third of all species represent either peregrines (14 species, 28.57%) or endemic (13 species, 26.53%). A higher fraction of the endemic species belongs to the Allolobophora and Dendrobaena genera. With the 13 endemic and some Balkanic-Alpine (4), Alpine-Dinaric (2), Illyric (Western Balkans) (2) species, it is proven that 42.85% of the total lumbricidae fauna shows an autochthonous character. These results represent another confirmation of particularity of this fauna and prove the need for further research in this area.